BUILDING ENVIRONMENTAL AWARENESS IN EARLY CHILDHOOD: LESSONS FROM SUSTAINABLE SCHOOL PRACTICES IN INDONESIA - Novika Adi Wibowo; Sumarmi Sumarmi; Alfyananda Kurnia Putra; Sigit Wibowo; A Riyan Rahman Hakiki; Batchuluun Yembuu; Annisa Anna Firdausi; Aura Julita Andiansyah; Intan Pratiwi; Dedy Zain Mochtar Asri (GeoEco, 2026)
Pollution and climate change are mostly caused by human activities that do not consider the environment or implement sustainable approaches. Thus, being conscious of the environment is an important part of teaching children the way to act in a manner that is good for the environment from an early age. This study attempts to assess the extent of environmental knowledge, attitudes, and behaviors among students in primary schools in SDN Pati Kidul 01, Indonesia, which implemented the Adiwiyata School Program. This study utilized a mixed-method approach including an exploratory sequential design, incorporating field observations, questionnaires, and documentation of school activities. The findings demonstrate that Adiwiyata programs such as "Healthy Classroom, Healthy Student", "Green School", and "Friday Cleanup Day" play significant roles in fostering students' environmental awareness through habituation of caring attitudes, actual actions, and environmental issue knowledge. Even while the majority of students exhibited strong pro-environmental behavior, there were still some small conceptual gaps in their knowledge of environmental issues. These findings show that incorporating ecological education into the regular school day successfully fosters a sense of environmental responsibility, establishing the Adiwiyata Program as a strategic plan for producing a future generation that is environmentally conscious.